Alloys, magnetic materials, bonded magnets, and methods for producing the same
By employing a RE-Fe-M-B alloy with controlled mass flow rates and quenching, the microstructural inhomogeneity issues in melt spinning are resolved, resulting in alloy ribbons with enhanced magnetic properties and uniformity.
Patent Information
- Application Number
- JP2024168002
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Current melt spinning techniques for producing iron-based rare earth magnets result in microstructural inhomogeneity, leading to decreased magnetic properties, and there is a need to improve manufacturing throughput without sacrificing homogeneity.
The use of a RE-Fe-M-B alloy formula with at least 80% RE by volume and an average crystal grain size of 20-40 nm for the B phase, combined with a controlled mass flow rate of 0.2-1.0 kg/min onto a rotating wheel for quenching, ensures a uniform ribbon microstructure.
This approach produces alloy ribbons with improved magnetic properties, including high remanence, energy product, and coercive force, while maintaining uniformity across the ribbon width.
Smart Images

Figure 2025004056000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates generally to alloys, magnetic materials, and bonded magnets. The present invention also relates to methods of making such alloys, magnetic materials, and bonded magnets. [Background technology]
[0002] Iron-based rare earth magnets are used in numerous applications, including computer hardware, automobiles, consumer electronics, motors, and home appliances. As technology advances, there is an ever-increasing need to produce magnets with improved magnetic performance. Therefore, it is desirable to achieve a process for producing iron-based rare earth alloys and magnets with improved magnetic performance.
[0003] There are several known methods for producing iron-based rare earth magnets. In such methods, the constituent metals are melted together and subsequently solidified. Solidification is achieved by various techniques including ingot casting, strip casting, and melt spinning. The solidified alloy can have the form of an ingot, flake, ribbon, or powder. Methods for producing magnets include sintering, hot pressing, hot deformation, and bonding.
[0004] The method used to manufacture an iron-based rare earth magnet affects its magnetic properties, and various process conditions in a method also affect the magnetic properties. In the melt spinning method, a molten alloy mixture is ejected onto the surface of a spinning or rotating wheel. Upon contact with the wheel surface, the molten alloy mixture forms ribbons that rapidly solidify into very fine nanoscale particles. The ribbons can be further crushed or ground and used to manufacture plastic bonded magnets.
[0005] It is well known that a very fine and uniform microstructure in melt-spun ribbons is important to achieve high magnetic properties. Although current melt spinning technology can produce very fine and nanoscale microstructures, a major drawback is that alloy ribbons produced by current melt spinning industry practices exhibit variations in microstructural uniformity between the edge and center regions of the ribbon when viewed through the ribbon's cross section. This microstructural inhomogeneity is undesirable as it leads to degradation of the alloy's magnetic properties. Therefore, improvements to melt spinning processes or products are generally attempted in two areas: (1) to eliminate the microstructural inhomogeneity, resulting in better magnetic properties, or (2) to increase manufacturing throughput without further sacrificing uniformity or properties. Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, there is a need to provide a magnetic material, and a method of forming such a magnetic material, that overcomes, or at least ameliorates, one or more of the above-mentioned disadvantages. [Means for solving the problem]
[0007] According to a first aspect of the present disclosure, there is provided a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, The alloy is at least 80% by volume of RE2Fe 14 Contains phase B, RE2Fe 14 The average grain size of the B phase is in the range of about 20 nm to about 40 nm, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the width between the center and the left and right ends of the alloy ribbon is RE2Fe 14 The alloys are provided, wherein the difference in average grain size of the B phase is less than 20%.
[0008] In a second aspect of the present disclosure, a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron), comprising the steps of: (i) discharging a melt of an alloy having a composition of formula (I) onto a rotating wheel at a mass flow rate ranging from about 0.2 kg / min to about 1.0 kg / min; (ii) quenching the melt using the rotating wheel to obtain the alloy ribbon; A method is provided, comprising:
[0009] Advantageously, the methods of the present disclosure may produce alloy ribbons having a substantially uniform ribbon microstructure.
[0010] More advantageously, the methods of the present disclosure may result in substantially uniform quenching of the alloy ribbon.
[0011] More advantageously, the method of the present disclosure provides a crystalline phase of REFe. 14 The alloys of the present disclosure may be produced having at least 80 vol.%, at least 90 vol.%, or at least 98 vol.% RE2Fe 14 It may contain a B phase.
[0012] In a third aspect of the present disclosure, there is provided a magnetic material comprising a powder of the alloy of the first aspect, or a powder of the alloy ribbon produced by the method of the second aspect.
[0013] In a fourth aspect of the present disclosure, there is provided a plastic bonded magnet comprising the magnetic material of the third aspect.
[0014] Advantageously, the magnetic materials or plastic bonded magnets of the present disclosure have improved magnetic properties, such as high remanence (B r ) value, high energy product [(BH) max ] value and high coercivity (H ci ) value.
[0015] The accompanying drawings illustrate embodiments of the present disclosure and serve to explain the principles of the presently disclosed embodiments, but it is to be understood that the drawings are designed for illustrative purposes only and are not intended as a definition of the limits of the invention. [Brief description of the drawings]
[0016] [Figure 1] 1 is a graph showing demagnetization curves of a: Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3) and b: Nd11.9Fe81Nb1.2B5.9 alloy (sample 1 in Table 3) at various mass flow rates. [Diagram 2] 1 is a graph showing (BH)max (kJ / m3) versus mass flow rate (kg / min) for a: Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3) and b: Nd11.9Fe81Nb1.2B5.9 alloy (sample 1 in Table 3). [Diagram 3] 1 is a graph showing wheel speed (m / sec) versus mass flow rate (kg / min) for a: Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3) and b: Nd11.9Fe81Nb1.2B5.9 alloy (sample 1 in Table 3). [Figure 4] 1 is a graph showing ribbon thickness (μm) or ribbon width (μm) versus mass flow rate (kg / min) for a: Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3) and b: Nd11.9Fe81Nb1.2B5.9 alloy (sample 1 in Table 3). [Diagram 5]1 is a graph showing the proportion (volume %) of the crystalline RE2Fe14B phase versus mass flow rate (kg / min) for the Nd11.6Fe80.3Co2.4B5.7 alloy (Sample 2 in Table 3). [Figure 6] 1 is a graph showing an X-ray diffraction pattern versus mass flow rate (kg / min) for a Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3). [Figure 7] 1 is a graph showing the average grain size (nm) of the RE2Fe14B phase versus the mass flow rate (kg / min) of the Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3). [Figure 8] FIG. 13 is a graph showing average grain size along the width (from the left edge to the center to the right edge) of an alloy ribbon for Nd11.6Fe80.3Co2.4B5.7 alloy (Sample 2 in Table 3) at mass flow rates of 0.2 kg / min, 0.5 kg / min, 0.8 kg / min, 1.3 kg / min, and 1.9 kg / min. [Figure 9] FIG. 1 shows scanning electron microscope (SEM) images of alloy ribbons (from left edge to center to right edge) for Nd11.6Fe80.3Co2.4B5.7 alloy (sample 2 in Table 3) at mass flow rates of 0.5 kg / min and 1.9 kg / min. [Figure 10] FIG. 2 is an exemplary diagram illustrating the zones that make up the width of the alloy ribbon of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] definition As used herein, the following terms shall have the following meanings.
[0018] As used herein, the term "rare earth" or "rare earth metal" refers to a rare earth element, which may be cerium (Ce), dysprosium (Dy), erbium (Er), europium (Eu), gadolinium (Gd), holmium (Ho), lanthanum (La), lutetium (Lu), neodymium (Nd), praseodymium (Pr), promethium (Pm), samarium (Sm), scandium (Sc), terbium (Tb), thulium (Tm), ytterbium (Yb), or yttrium (Y).
[0019] The term "substantially" does not exclude "completely", for example a composition that is "substantially free" of Y may be completely free of Y. Where necessary, the term "substantially" can be excluded from the definition of the present invention.
[0020] Unless otherwise indicated, the terms "comprising" and "comprise," as well as grammatical variations thereof, are intended to denote "open" or "inclusive" language that not only includes the recited elements, but also permits the inclusion of additional, unrecited elements.
[0021] The term "about" as used herein in connection with the concentration of a formula component typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0022] Throughout this disclosure, certain embodiments may be disclosed in the form of a range. It is understood that the description in the form of a range is merely for convenience and brevity, and should not be interpreted as an indefinite limit on the disclosed range. Thus, the description of a range should be considered to have all possible subranges specifically disclosed, as well as individual numerical values within that range. For example, the description of a range of 1 to 6 should be considered to have specifically disclosed subranges such as 1 to 3, 1 to 4, 1 to 5, 2 to 4, 2 to 6, 3 to 6, etc., as well as individual numerical values within that range, for example, 1, 2, 3, 4, 5, and 6. This applies regardless of the breadth of the range.
[0023] Certain embodiments may be broadly and generically described herein. Each of the narrower species and subgeneric groupings falling within the generic disclosure also form part of this disclosure. This includes the generic description of an embodiment with a condition or negative limitation excluding any subject matter from the genus, regardless of whether the excluded matter is specifically recited herein.
[0024] Detailed Disclosure of the Embodiments As mentioned above, bonded magnets, such as iron-based rare earth magnets, are used in numerous applications including computer hardware, automobiles, consumer electronics, and home appliances. Such magnets have a high BH max Value, High B r value, and high H ci It is advantageous to have a value.
[0025] Improved magnetic performance can be achieved by a magnetic material with a uniform microstructure. In conventional melt spinning processes, it is difficult to form alloy ribbons with a uniform microstructure between the ends of the ribbon and the center of the ribbon because of differences in cooling rates along the cross-sectional area of the ribbon, which leads to inhomogeneity in the microstructure.
[0026] The present inventors have surprisingly discovered that low mass flow rates of melt delivered to the surface of a melt spinning wheel can produce alloy ribbons having a substantially uniform microstructure. Such alloy ribbons produced in accordance with the present invention have a high BH max Value, High B r value, and high H ci It has the advantage of showing the value.
[0027] Disclosed below are exemplary, non-limiting embodiments of the disclosed alloys, magnetic materials, bonded magnets, and methods of making same.
[0028] The present invention relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and and B is boron.
[0029] As used herein, the RE, Fe, M, and B components in formula (I) are understood to be present in various atomic % which add up to 100 atomic %.
[0030] The present invention relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, At least 80% by volume of RE2Fe 14 An alloy is provided, comprising a B phase.
[0031] The present invention also relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, The alloy is at least 80% by volume of RE2Fe 14 Phase B is included, and RE2Fe 14 The alloy has an average crystal grain size of the B phase in the range of about 20 nm to about 40 nm.
[0032] Further, the present invention relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, The alloy is at least 80% by volume of RE2Fe 14 Phase B is included, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the width between the center and the left and right ends of the alloy ribbon is RE2Fe 14 The alloy has a difference in average grain size of the B phase of less than 20%.
[0033] The present invention also relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, The alloy is at least 80% by volume of RE2Fe 14 Contains phase B, RE2Fe 14 The average grain size of the B phase is in the range of about 20 nm to about 40 nm, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the width between the center and the left and right ends of the alloy ribbon is RE2Fe 14 The alloy has a difference in average grain size of the B phase of less than 20%.
[0034] The present invention also relates to a compound of formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and where x, y, and z are in atomic percent, and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.0; At least 80% by volume of RE2Fe 14 An alloy is provided, comprising a B phase.
[0035] Further, the present invention relates to a compound of formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and where x, y, and z are in atomic percent, and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.0; The alloy is at least 80% by volume of RE2Fe 14 Phase B is included, and RE2Fe 14 The alloy has an average crystal grain size of the B phase in the range of about 20 nm to about 40 nm.
[0036] The present invention also relates to a compound of formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and where x, y, and z are in atomic percent, and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.0; The alloy is at least 80% by volume of RE2Fe 14 Phase B is included, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the width between the center and the left and right ends of the alloy ribbon is RE2Fe 14 The alloy has a difference in average grain size of the B phase of less than 20%.
[0037] The present invention also relates to a compound of formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron, and where x, y, and z are in atomic percent, and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.0; The alloy is at least 80% by volume of RE2Fe 14 Contains phase B, RE2Fe 14 The average grain size of the B phase is in the range of about 20 nm to about 40 nm, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the width between the center and the left and right ends of the alloy ribbon is RE2Fe 14 The alloy has a difference in average grain size of the B phase of less than 20%.
[0038] The above alloy contains RE2Fe as the main phase. 14 %.
[0039] The alloy is at least 80% by volume of RE2Fe 14 The alloys of the present disclosure may include at least 80 vol%, at least 81 vol%, at least 82 vol%, at least 83 vol%, at least 84 vol%, at least 85 vol%, at least 86 vol%, at least 87 vol%, at least 88 vol%, at least 89 vol%, at least 90 vol%, at least 91 vol%, at least 92 vol%, at least 93 vol%, at least 94 vol%, at least 95 vol%, at least 96 vol%, at least 97 vol%, at least 90 vol%, or at least 99 vol% RE2Fe 14The alloy of the present disclosure may include a phase B. The alloy of the present disclosure may include a phase B having a crystal structure of about 80% by volume to about 99% by volume, about 81% by volume to about 99% by volume, about 82% by volume to about 99% by volume, about 83% by volume to about 99% by volume, about 84% by volume to about 99% by volume, about 85% by volume to about 99% by volume, about 86% by volume to about 99% by volume, about 87% by volume to about 99% by volume, about 88% by volume to about 99% by volume, about 89% by volume to about 99% by volume, about 90% by volume to about 99% by volume, or about 91% by volume to about 99% by volume, about 92% by volume to about 99% by volume, about 93% by volume to about 99% by volume, about 94% by volume to about 99% by volume, about 95% by volume to about 99% by volume, about 96% by volume to about 99% by volume, about 97% by volume to about 99% by volume, about 98 ...9% by volume to about 99% by volume. %, about 80 vol% to about 98 vol%, about 80 vol% to about 97 vol%, about 80 vol% to about 96 vol%, about 80 vol% to about 95 vol%, about 80 vol% to about 94 vol%, about 80 vol% to about 93 vol%, about 80 vol% to about 92 vol%, about 80 vol% to about 91 vol%, about 80 vol% to about 90 vol%, about 80 vol% to about 89 vol%, about 80 vol% to about 88 vol%, about 80 vol% to about 87 vol%, about 80 vol% to about 86 vol%, about 80 vol% to about 85 vol%, about 80 vol% to about 84 vol%, about 80 vol% to about 83 vol%, about 80 vol% to about 82 vol%, about 80 vol% to about 81 vol%, and about 97 vol% to about 99 vol% of RE2Fe. 14 %, about 80 vol.%, about 81 vol.%, about 82 vol.%, about 83 vol.%, about 84 vol.%, about 85 vol.%, about 86 vol.%, about 87 vol.%, about 88 vol.%, about 89 vol.%, or about 90 vol.%, about 91 vol.%, about 92 vol.%, about 93 vol.%, about 94 vol.%, about 95 vol.%, about 96 vol.%, about 97 vol.%, about 98 vol.%, about 99 vol.% REFe. 14 B phase, or any range or value therein. 14 It may contain a B phase.
[0040] RE2Fe of the above alloy 14Phase B has a diameter in the range of about 20 nm to about 40 nm, or about 21 nm to about 40 nm, about 22 nm to about 40 nm, about 23 nm to about 40 nm, about 24 nm to about 40 nm, about 25 nm to about 40 nm, about 26 nm to about 40 nm, about 27 nm to about 40 nm, about 28 nm to about 40 nm, about 29 nm to about 40 nm, about 30 nm to about 40 nm, about 31 nm to about 40 nm, about 32 nm to about 40nm, about 33nm to about 40nm, about 34nm to about 40nm, about 35nm to about 40nm, about 36nm to about 40nm, about 37nm to about 40nm, about 38nm to about 40nm, about 39 nm~about 40nm, about 20nm~about 39nm, about 20nm~about 38nm, about 20nm~about 37nm, about 20nm~about 36nm, about 20nm~about 35nm, about 20nm~about 34nm, about 20 nm to about 33 nm, about 20 nm to about 32 nm, about 20 nm to about 31 nm, about 20 nm to about 30 nm, about 20 nm to about 29 nm, about 20 nm to about 28 nm, about 20 nm to about 27 nm, about 20 nm to about 26 nm, about 20 nm to about 25 nm, about 20 nm to about 24 nm, about 20 nm to about 23 nm, about 20 nm to about 22 nm, about 20 nm to about 21 nm, or about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm, about 25 nm, about 26 nm, about 27 nm, about 28 nm, about 29 nm, about 30 nm, about 31 nm, about 32 nm, about 33 nm, about 34 nm, about 35 nm, about 36 nm, about 37 nm, about 38 nm, about 39 nm, about 40 nm, or any range or value therein.
[0041] The alloy may be a quenched alloy.The alloy may be an alloy ribbon.The alloy may be a quenched alloy ribbon.
[0042] The alloy ribbon may have a width measured from the left end of the ribbon to the right end of the ribbon of about 1 mm to about 5 mm, which may be about 1 mm to about 5 mm, about 1 mm to about 4 mm, about 1 mm to about 3 mm, about 1 mm to about 2 mm, about 2 mm to about 5 mm, about 3 mm to about 5 mm, about 4 mm to about 5 mm, or about 1 mm, about 2 mm, about 3 mm, about 4 mm, about 5 mm, or any value or range within the range.
[0043] The "left end" of the alloy ribbon may be located at the leftmost portion of the alloy ribbon and may comprise from greater than 0% to about 10% of the width of the alloy ribbon. The "left end" of the alloy ribbon can be greater than 0% to about 10%, about 1% to about 10%, about 2% to about 10%, about 3% to about 10%, about 4% to about 10%, about 5% to about 10%, about 6% to about 10%, about 7% to about 10%, about 8% to about 10%, about 9% to about 10%, greater than 0% to about 9%, greater than 0% to about 8%, greater than 0% to about 7%, greater than 0% to about 6%, greater than 0% to about 5%, greater than 0% to about 4%, greater than 0% to about 3%, greater than 0% to about 2%, or greater than 0%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, or any value or range therein. This means that for a 1 mm wide alloy ribbon, the left end of the ribbon is between about 0 mm and 0.1 mm. For a 5 mm wide alloy ribbon, the left end of the ribbon is between about 0 mm and 0.5 mm.
[0044] The "right end" of the alloy ribbon may be located at the rightmost portion of the alloy ribbon and may comprise greater than 0% to about 10% of the width of the alloy ribbon. The "right end" of the alloy ribbon can be greater than 0% to about 10%, about 1% to about 10%, about 2% to about 10%, about 3% to about 10%, about 4% to about 10%, about 5% to about 10%, about 6% to about 10%, about 7% to about 10%, about 8% to about 10%, about 9% to about 10%, greater than 0% to about 9%, greater than 0% to about 8%, greater than 0% to about 7%, greater than 0% to about 6%, greater than 0% to about 5%, greater than 0% to about 4%, greater than 0% to about 3%, greater than 0% to about 2%, or greater than 0%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, or any value or range therein. This means that for a 1 mm wide alloy ribbon, the right end of the ribbon is between about 0 mm and 0.1 mm. For a 5 mm wide alloy ribbon, the right end of the ribbon is between about 0 mm and 0.5 mm.
[0045] The "center" of the alloy ribbon may be located at the center of the alloy ribbon and may comprise about 1% to about 40% of the width of the alloy ribbon (i.e., about 0.5% to about 20% of the width on either side of the centerline of the alloy ribbon).The "center end" of the alloy ribbon is about 1% to about 40%, about 2% to about 40%, about 3% to about 40%, about 4% to about 40%, about 5% to about 40%, about 6% to about 40%, about 7% to about 40%, about 8% to about 40%, about 9% to about 40%, about 10% to about 40%, about 11% to about 40%, about 12% to about 40%, about 13% to about 40%, about 14% to about 40%, about 15% to about 40%, about 16% to about 40%, about 17% to about 40%, about 18% to about 40%, about 19% to about 40%, about 20% to about 40%, about 21% to about 40%, about 22% to about 40%, about 23% to about 40%, about 24% ~ about 40%, about 25% to about 40%, about 26% to about 40%, about 27% to about 40%, about 28% to about 40%, about 29% to about 40%, about 30% to about 40%, about 31% to about 40%, about 32% to about 40%, about 33% to about 40%, about 34% to about 40%, about 35% to about 40%, about 36% to about 40%, about 37% to about 40%, about 38% to about 40%, about 39% to about 40%, about 1% to about 39%, about 1% to about 38%, about 1% to about 37%, about 1% to about 36%, about 1% to about 35%, about 1% to about 34%, about 1% to about 33%, about 1% to about 32%, about 1% to about 31%, about % to about 30%, about 1% to about 29%, about 1% to about 28%, about 1% to about 27%, about 1% to about 26%, about 1% to about 25%, about 1% to about 24%, about 1% to about 23%, about 1% to about 22%, about 1% to about 21%, about 1% to about 20%, about 1% to about 19%, about 1% to about 18%, about 1% to about 17%, about 1% to about 16%, about 1% to about 15%, about 1% to about 14%, about 1% to about 13%, about 1% to about 12%, about 1% to about 11%, about 1% to about 10%, about 1% to about 9%, about 1% to about 8%, about 1% to about 7%, about 1% to about 6%, about 1% to about 5%, about 1% to about 4%, about 1% to about It may be about 3%, about 1% to about 2%, or about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, or any value or range within that range.This means that for a 1 mm wide alloy ribbon, the center of the ribbon is about 0.01 mm to about 0.4 mm. For a 5 mm wide alloy ribbon, the right edge of the ribbon is about 0.05 mm to about 2.0 mm.
[0046] Along the width of the alloy ribbon, between the left end and the center, there may be a portion referred to herein as a "center left" portion. Along the width of the alloy ribbon, between the center and the right end, there may be a portion referred to herein as a "center right" portion.
[0047] The alloy ribbon may have a thickness of about 20 μm to about 50 μm. This thickness is about 20 μm to about 50 μm, about 22 μm to about 50 μm, about 24 μm to about 50 μm, about 26 μm to about 50 μm, about 28 μm to about 50 μm, about 30 μm to about 50 μm, about 32 μm to about 50 μm, about 34 μm to about 50 μm, about 36 μm to about 50 μm, about 38 μm to about 50 μm, about 40 μm to about 50 μm, about 42 μm to about 50 μm, about 44 μm to about 50 μm, about 46 μm to about 50 μm, about 48 μm to about 50 μm, about 20 μm to about 48 μm, about 20 μm to about 46 μm, about 20 μm to about 44 μm, about 20 μm to about 42 μm, It can be about 20 μm to about 40 μm, about 20 μm to about 38 μm, about 20 μm to about 36 μm, about 20 μm to about 34 μm, about 20 μm to about 32 μm, about 20 μm to about 30 μm, about 20 μm to about 28 μm, about 20 μm to about 26 μm, about 20 μm to about 24 μm, about 20 μm to about 22 μm, or about 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, 32 μm, 34 μm, 36 μm, 38 μm, 40 μm, 42 μm, 44 μm, 46 μm, 48 μm, 50 μm, or any value or range within that range.
[0048] RE2Fe in the center of the above alloy ribbon 14The average particle size of the B phase is in the range of about 25 nm to about 40 nm, or about 26 nm to about 40 nm, about 27 nm to about 40 nm, or about 28 nm to about 40 nm. m, about 29nm to about 40nm, about 30nm to about 40nm, about 31nm to about 40nm, about 32nm to about 40nm, about 33nm to about 40nm, Approximately 34nm to approximately 40nm, approximately 35nm to approximately 40nm, approximately 36nm to approximately 40nm, approximately 37nm to approximately 40nm, approximately 38nm to approximately 40nm, approximately 39nm to about 40nm, about 25nm to about 39nm, about 25nm to about 38nm, about 25nm to about 37nm, about 25nm to about 36nm, about 25 nm to about 35 nm, about 25 nm to about 34 nm, about 25 nm to about 33 nm, about 25 nm to about 32 nm, about 25 nm to about 31 nm, about 25 nm to about 30 nm, about 25 nm to about 29 nm, about 25 nm to about 28 nm, about 25 nm to about 27 nm, about 25 nm to about 26 nm, or about 25 nm, about 26 nm, about 27 nm, about 28 nm, about 29 nm, about 30 nm, about 31 nm, about 32 nm, about 33 nm, about 34 nm, about 35 nm, about 36 nm, about 37 nm, about 38 nm, about 39 nm, about 40 nm, or any range or any value within that range.
[0049] RE2Fe at the left end of the alloy ribbon 14 The average particle size of the B phase is approximately 20 nm to approximately 30 nm, approximately 21 nm to approximately 30 nm, approximately 22 nm to approximately 30 nm, approximately 23 nm to approximately 30 nm, approximately 24 nm to approximately 30 nm, approximately 25 nm to approximately 30 nm, Approximately 26nm to approximately 30nm, approximately 27nm to approximately 30nm, approximately 28nm to approximately 30nm, approximately 29nm to approximately 30nm, approximately 20nm to approximately 29nm, approximately 20nm to approximately 28nm, approximately 20nm to approximately 27nm, approximately The thickness of the RE2Fe alloy ribbon between the center and the left and right ends can be about 20 nm to about 26 nm, about 20 nm to about 25 nm, about 20 nm to about 24 nm, about 20 nm to about 23 nm, about 20 nm to about 22 nm, about 20 nm to about 21 nm, or about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm, about 25 nm, about 26 nm, about 27 nm, about 28 nm, about 29 nm, about 30 nm, or any range or value therein. 14 The difference in the average grain size of the B phase may be in the range of 20% or less.
[0050] RE2Fe at the right end of the alloy ribbon 14 The average particle size of the B phase is approximately 20 nm to approximately 30 nm, approximately 21 nm to approximately 30 nm, approximately 22 nm to approximately 30 nm, approximately 23 nm to approximately 30 nm, approximately 24 nm to approximately 30 nm, approximately 25 nm to approximately 30 nm, Approximately 26nm to approximately 30nm, approximately 27nm to approximately 30nm, approximately 28nm to approximately 30nm, approximately 29nm to approximately 30nm, approximately 20nm to approximately 29nm, approximately 20nm to approximately 28nm, approximately 20nm to approximately 27nm, approximately The thickness of the RE2Fe alloy ribbon between the center and the left and right ends can be about 20 nm to about 26 nm, about 20 nm to about 25 nm, about 20 nm to about 24 nm, about 20 nm to about 23 nm, about 20 nm to about 22 nm, about 20 nm to about 21 nm, or about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm, about 25 nm, about 26 nm, about 27 nm, about 28 nm, about 29 nm, about 30 nm, or any range or value therein. 14 The difference in the average grain size of the B phase may be in the range of 20% or less.
[0051] The RE2Fe between the center of the alloy ribbon and the left and right ends 14The difference in the average particle size of the B phase is in the range of about 20% or less, less than about 19%, less than about 18%, less than about 17%, less than about 16%, less than about 15%, less than about 14%, less than about 13%, less than about 12%, less than about 11%, less than about 10%, less than about 9%, less than about 8%, less than about 7%, less than about 6%, less than about 5%, less than about 4%, less than about 3%, less than about 2%, less than about 1%, or about 1% to about 20%, about 2% to about 20%, about 3% to about 20%, about 4% to about 20%, about 5% to about 20%, about 6% to about 20%, about 7% to about 20%, about 8% to about 20%, about 9% to about 20%, about 10% to about 20%, about 11% to about 20%, about 12% to about 20%, about 13% to about 20%, about 14% to about 20%, about 15% to about 20%, about 16% to about 20%, about 17% to about 20%, about 18% to about 20%, about 19% to about 20%, about 1% to about 19%, about 1% to about 18%, about 1% to about 17%, about 1% to about 16%, about 1% to about 15%, about 1% to about 14%, about 1% to about 13%, about 1% to about 12%, about 1% to about 11%, about 1% to about 10%, about 1% to about 9%, about 1% to about 8%, about 1% to about 7%, about 1% to about 6%, about 1% to about 5% %, about 1% to about 4%, about 1% to about 3%, about 1% to about 2%, or about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or any value or range therein.
[0052] In formula (I) or formula (Ia), RE can be one or more rare earth metals. RE can be one, two, three, four, or five rare earth metals.
[0053] In formula (I) or formula (Ia), RE can be one or more rare earth metals selected from the group consisting of lanthanum (La), cerium (Ce), neodymium (Nd), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), and ytterbium (Yb).
[0054] In formula (I) or formula (Ia), RE can be one, two, or three rare earth metals selected from the group consisting of Nd, Pr, La, and Ce.
[0055] In the formula (I) or (Ia), RE is the following: (i) Nd, (ii) Nd, Pr, (iii) Nd, Pr, La, (iv) Nd, Pr, Ce, (v) Nd, Pr, Ce, La, (vi) Nd, La, (vii) Nd, Ce, (viii) Nd, Ce, La, (ix) Pr, (x) Pr, La, (xi) Pr, Ce, and (xii) Pr, La, Ce The compound may be selected from the group consisting of:
[0056] In formula (I) or formula (Ia), M can be absent or one or more metals. M can be absent or one, two, three, four, or five rare earth metals. M can be a transition metal or a refractory metal.
[0057] In formula (I) or formula (Ia), M can be absent or one or more metals selected from the group consisting of zirconium (Zr), niobium (Nb), molybdenum (Mo), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), hafnium (Hf), tantalum (Ta), tungsten (W), cobalt (Co), copper (Cu), gallium (Ga), and aluminum (Al).
[0058] M can be one or more metals selected from the group consisting of Nb, Co, Al, and Zr.
[0059] In formula (Ia), x can be 8.0≦x≦14.0. x can be about 8.0 to about 14.0, about 8.5 to about 14.0, about 9.0 to about 14.0, about 9.5 to about 14.0, about 10.0 to about 14.0, about 10.5 to about 14.0, about 11.0 to about 14.0, about 11.5 to about 14.0, about 12.0 to about 14.0, about 12.5 to about 14.0, about 13.0 to about 14.0, about 13.5 to about 14.0, about 8.0 to about 13.5, about 8.0 to about 1 3.0, about 8.0 to about 12.5, about 8.0 to about 12.0, about 8.0 to about 11.5, about 8.0 to about 11.0, about 8.0 to about 10.5, about 8.0 to about 10.0, about 8.0 to about 9.5, about 8.0 to about 9.0, about 8.0 to about 8.5, or about 8.0, about 8.1, about 8.2, about 8.3, about 8.4, about 8.5, about 8.6, about 8.7, about 8.8, about 8.9, about 9.0, about 9.1 , about 9.2, about 9.3, about 9.4, about 9.5, about 9.5, about 9.6, about 9.7, about 9.8, about 9.9, about 10.0, about 10.1, about 10.2, about 10.3, about 10.4, about 10.5, about 10.6, about 10.7, about 10.8, about 10.9, about 11.0, about 11.1, about 11.2, about 11.3, about 11.4, about 11.5, about 11.6, about 11.7, about 11.8, about It can be about 11.9, about 12.0, about 12.1, about 12.2, about 12.3, about 12.4, about 12.5, about 12.6, about 12.7, about 12.8, about 12.9, about 13.0, about 13.1, about 13.2, about 13.3, about 13.4, about 13.5, about 13.6, about 13.7, about 13.8, about 13.9, about 14.0, or any value or range therein.
[0060] In formula (Ia), y can be 0≦y≦2.0. y can be about 0 to about 2.0, about 0 to about 1.8, about 0 to about 1.6, about 0 to about 1.4, about 0 to about 1.2, about 0 to about 1.0, about 0 to about 0.8, about 0 to about 0.6, about 0 to about 0.4, about 0 to about 0.2, about 0.2 to about 2.0, about 0.4 to about 2.0, about 0.6 to about 2.0, about 0.8 to about 2.0, about 1.0 to about 2.0, about 1.2 to about 2.0, about 1.4 to about 2.0, It can be about 1.6 to about 2.0, about 1.8 to about 2.0, or 0, about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, or any value or range within that range.
[0061] In formula (Ia), z can be 5.0≦z≦7.0. z can be about 5.0 to about 7.0, about 5.0 to about 6.8, about 5.0 to about 6.6, about 5.0 to about 6.4, about 5.0 to about 6.2, about 5.0 to about 6.0, about 5.0 to about 5.8, about 5.0 to about 5.6, about 5.0 to about 5.4, about 5.0 to about 5.2, about 5.2 to about 7.0, about 5.4 to about 7.0, about 5.6 to about 7.0, about 5.8 to about 7.0, about 6.0 to about 7.0, about 6.2 to about 7.0, about 6.4 to about 7 0, about 6.6 to about 7.0, about 6.8 to about 7.0, or about 5.0, or about 5.1, about 5.2, or about 5.3, about 5.4, or about 5.5, about 5.6, or about 5.7, about 5.8, or about 5.9, about 6.0, about 6.1, about 6.2, about 6.3, about 6.4, about 6.5, about 6.6, about 6.7, about 6.8, about 6.9, about 7.0, or any value or range within that range.
[0062] The alloys are as follows: (i) Nd-Fe-Nb-B, (ii) Nd-Fe-Co-B, (iii) (NdPrLa)-Fe-Al-B, (iv) (NdPr)-Fe-Zr-B, (v) (NdPrCe)-Fe-Zr-B, (vi) Nd-Fe-Co-B, (vii) Nd-Fe-B, (viii) (NdPr)-Fe-B, (ix) (NdPrLaCe)-Fe-B, (x) (NdPr)-Fe-Co-B, and (xi)(NdPr)-Fe-Nb-B The composition may be selected from the group consisting of:
[0063] The boron content of the alloy can be less than about 10 atomic %, such as less than about 10 atomic %, less than about 9 atomic %, less than about 8 atomic %, less than about 7 atomic %, less than about 6 atomic %, less than about 5 atomic %, less than about 4 atomic %, less than about 3 atomic %, less than about 2 atomic %, less than about 1 atomic %, or between about 1 atomic % and about 10 atomic %, between about 2 atomic % and about 10 atomic %, between about 3 atomic % and about 10 atomic %, between about 4 atomic % and about 10 atomic %, between about 5 atomic % and about 10 atomic %, between about 6 atomic % and about 10 atomic %, between about 7 atomic % and about 10 atomic %, between about 8 atomic % and about 10 atomic %, between about 9 atomic % and about 10 atomic %, or between about 10 atomic % and about 10 atomic %. It can be in the range of about 10 atomic %, about 1 atomic % to about 9 atomic %, about 1 atomic % to about 8 atomic %, about 1 atomic % to about 7 atomic %, about 1 atomic % to about 6 atomic %, about 1 atomic % to about 5 atomic %, about 1 atomic % to about 4 atomic %, about 1 atomic % to about 3 atomic %, about 1 atomic % to about 2 atomic %, or about 1 atomic %, about 2 atomic %, about 3 atomic %, about 4 atomic %, about 5 atomic %, about 6 atomic %, about 7 atomic %, about 8 atomic %, about 9 atomic %, about 10 atomic %, or any range or any value within that range.
[0064] The alloys are as follows: (i)Nd 11.9 Fe 81.0 Nb 1.2 B 5.9 , (ii)Nd 11.6 Fe 80.3 Co 2.4 B 5.7 , (iii) (Nd 0.75 Pr 0.25 ) 9.9 La 1.9 Fe 81.6 Al 1.0 B 5.6 , (iv)(Nd 0.75 Pr0.25 ) 10.8 Fe 81.9 Zr 1.0 B 6.3 , (v)(Nd 0.75 Pr 0.25 ) 6.8 Ce 4.6 Fe 81.3 Zr 1.0 B 6.3 , (vi)N.D. 12.0 Fe 76.3 Co 5.9 B 5.8 , (vii)N.D. 11.7 Fe 82.6 B 5.7 , (viii)(Nd 0.75 Pr 0.25 ) 11.2 Fe 83.4 B 5.4 , (ix)(Nd 0.75 Pr 0.25 ) 10.4 Fe 84.1 B 5.5 , and (x)(Nd 0.75 Pr 0.25 ) 6.0 La 3.0 Ce 3.0 Fe 81.8 B 6.2 The composition may be selected from the group consisting of:
[0065] The present invention also relates to a compound of formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and B is boron), comprising the steps of: (i) discharging an alloy melt having a composition of formula (I) onto a rotating wheel at a mass flow rate ranging from about 0.2 kg / min to about 1.8 kg / min, preferably from about 0.2 kg / min to about 1.0 kg / min; (ii) quenching the melt using the rotating wheel to obtain an alloy ribbon; The present invention relates to a method comprising the steps of:
[0066] The present invention also relates to a compound of formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and x, y, and z are atomic percent, and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.0, comprising the steps of: (i) discharging an alloy melt having a composition of formula (Ia) onto a rotating wheel at a mass flow rate ranging from about 0.2 kg / min to about 1.8 kg / min, preferably from about 0.2 kg / min to about 1.0 kg / min; (ii) quenching the melt using the rotating wheel to obtain an alloy ribbon; The present invention relates to a method comprising the steps of:
[0067] The present invention also relates to alloy ribbons produced by the methods disclosed herein.
[0068] The mass flow rate of the melt flowing onto the rotating wheel can range from about 0.2 kg / min to about 1.90 kg / min. The mass flow rate can range from about 0.30 kg / min to about 1.90 kg / min, about 0.40 kg / min to about 1.90 kg / min, about 0.50 kg / min to about 1.90 kg / min, about 0.60 kg / min to about 1.90 kg / min, about 0.70 kg / min to about 1.90 kg / min, about 0.80 kg / min to about 1.90 kg / min, about 0.90 kg / min to about 1.90 kg / min, about 1.00 kg / min to about 1.90 kg / min, about 1.10 kg / min to about 1.90 kg / min, about 1.20 kg / min to about 1.90 kg / min, about 1.30 kg / min to about 1.90 kg / min, about 1.40 kg / min, about 1.50 kg / min to about 1.90 kg / min, about 1.60 kg / min to about 1.90 kg / min, about 1.70 kg / min to about 1.90 kg / min, about 1.80 kg / min to about 1.90 kg / min, about 1.9 ...90 kg / min to about 1.90 kg / min, about 1.10 kg / min to about 1.90 kg / min, about 1.20 kg / min to about 1.90 kg / min, about 1.30 kg / min to about 1.90 kg / min, about 1.40 kg / min, about 1.50 kg / min min to about 1.90 kg / min, about 1.50 kg / min to about 1.90 kg / min, about 1.60 kg / min to about 1.90 kg / min, about 1.70 kg / min to about 1.90 kg / min, about 1.80 kg / min to about 1.90 kg / min, about 0.20 kg / min to about 1.80 kg / min, about 0.20 kg / min to about 1.70 kg / min, about 0.20 kg / min to about 1.60 kg / min, about 0.20 kg / min to about 1.50 kg / min, about 0.20 kg / min to about 1.40 kg / min, about 0.20 kg / min to about 1.30 kg / min, about 0.20 kg / min to about 1.20 kg / min, about 0. 20kg / min to about 1.10kg / min, about 0.20kg / min to about 1.00kg / min, about 0.20kg / min to about 0.90kg / min, about 0.20kg / min to about 0.80kg / min, about 0.20kg / min to about 0.70kg / min, about 0.20kg / min to about 0.60kg / min, about 0.20kg / min to about 0.50kg / min, about 0.20kg / min to about 0.40kg / min, about 0.20kg / min to about 0.30kg / min, about 0.20kg / min to about 1.00kg / min, about 0.30kg / min to about 1.00kg / min, about 0.40kg / min to about 1.00kg / min min, about 0.50kg / min to about 1.00kg / min, about 0.60kg / min to about 1.00kg / min, about 0.70kg / min to about 1.00kg / min, about 0.80kg / min to about 1.00kg / min, about 0.90kg / min to about 1.00kg / min, about 0.20kg / min to about 0.90kg / min, about 0.20kg / min to about 0.80kg / min, about 0.20kg / min to about 0.70kg / min, about 0.20kg / min to about 0.60kg / min, about 0.20kg / min to about 0.50kg / min, about 0.20kg / min to about 0.40kg / min, about 0.20kg / min to about 0.The rate can be in the range of 30 kg / min, or about 0.20 kg / min, about 0.30 kg / min, about 0.40 kg / min, about 0.50 kg / min, about 0.60 kg / min, about 0.70 kg / min, about 0.80 kg / min, about 0.90 kg / min, about 1.00 kg / min, about 1.10 kg / min, about 1.20 kg / min, about 1.30 kg / min, about 1.40 kg / min, about 1.50 kg / min, about 1.60 kg / min, about 1.70 kg / min, about 1.80 kg / min, about 1.90 kg / min, or any range or value therein.
[0069] The present inventors have surprisingly discovered that ejecting the melt onto the surface of a melt spinning or rotating wheel at a low mass flow rate can result in alloy ribbons with a more uniform microstructure and higher magnetic performance.
[0070] The melt discharged onto the rotating wheel can be further optimally quenched by adjusting the wheel speed. The wheel may be rotated at a speed in the range of about 20 m / s to about 45 m / s, about 25 m / s to about 45 m / s, 30 m / s to about 45 m / s, 35 m / s to about 45 m / s, 40 m / s to about 45 m / s, 20 m / s to about 40 m / s, 20 m / s to about 35 m / s, 20 m / s to about 30 m / s, 20 m / s to about 25 m / s, or about 20 m / s, or about 21 m / s, or about 22 m / s, or about 23 m / s, or about 24 m / s, or about 25 m / s, or about 25 m / s, or about 26 m / s, or about 27 m / s, or about 28 m / s, or about 29 m / s, or about 30 m / s, or about 31 m / s, or about 32 m / s, or about 33 m / s, or about 34 m / s, or about 35 m / s, or about 36 m / s, or about 37 m / s, or about 38 m / s, or about 39 m / s, or about 40 ... or about 26 m / s, or about 27 m / s, or about 28 m / s, or about 29 m / s, about 30 m / s, about 31 m / s, about 32 m / s, about 33 m / s, about 34 m / s, about 35 m / s, about 36 m / s, about 37 m / s, about 38 m / s, about 39 m / s, about 40 m / s, about 41 m / s, about 42 m / s, about 43 m / s, about 44 m / s, about 45 m / s, or any range or value therein.
[0071] When the mass flow rate of the melt discharged onto the rotating wheel is 0.20 kg / min, the wheel can rotate at a speed ranging from about 20 m / s to about 25 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 0.50 kg / min, the wheel can rotate at a speed ranging from about 25 m / s to about 30 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 0.80 kg / min, the wheel can rotate at a speed ranging from about 30 m / s to about 35 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 1.30 kg / min, the wheel can rotate at a speed ranging from about 35 m / s to about 40 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 1.90 kg / min, the wheel can rotate at a speed ranging from about 40 m / s to about 45 m / s.
[0072] When the mass flow rate of the melt discharged onto the rotating wheel is 0.20 kg / min, the wheel can rotate at a speed of about 20 m / s, about 21 m / s, about 22 m / s, about 23 m / s, about 24 m / s, or about 25 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 0.50 kg / min, the wheel can rotate at a speed in the range of about 25 m / s, about 26 m / s, about 27 m / s, about 28 m / s, about 29 m / s, or about 30 m / s. When the mass flow rate of the melt discharged onto the rotating wheel is 0.80 kg / min, the wheel can rotate at a speed in the range of about 30 m / s, about 31 m / s, about 32 m / s, about 33 m / s, about 34 m / s, or about 35 m / s. When the mass flow rate of melt dispensed onto the rotating wheel is 1.30 kg / min, the wheel can rotate at a speed in the range of about 35 m / s, about 36 m / s, about 37 m / s, about 38 m / s, about 39 m / s, or about 40 m / s. When the mass flow rate of melt dispensed onto the rotating wheel is 1.90 kg / min, the wheel can rotate at a speed in the range of about 40 m / s, about 41 m / s, about 42 m / s, about 43 m / s, about 44 m / s, or about 45 m / s.
[0073] The melt can be discharged onto the rotating wheel through one or more nozzles, and the mass flow rate of the melt exiting onto the rotating wheel can be controlled by controlling the diameter of the nozzles.
[0074] The diameter of the one or more nozzles may be in the range of about 0.5 mm to about 1.4 mm, or about 0.6 mm to about 1.4 mm, about 0.7 mm to about 1.4 mm, about 0.8 mm to about 1.4 mm, about 0.9 mm to about 1.4 mm, about 1.0 mm to about 1.4 mm, about 1.1 mm to about 1.4 mm, about 1.2 mm to about 1.4 mm, about 1.3 mm to about 1.4 mm, about 0.5 mm to about 1.3 mm, about 0.5 mm to about 1.2 mm, about 0.5 mm to about 1.2 mm, about 0.5 mm to about 1.5 ... It can be about 1.1 mm, about 0.5 mm to about 1.0 mm, about 0.5 mm to about 0.9 mm, about 0.5 mm to about 0.8 mm, about 0.5 mm to about 0.7 mm, about 0.5 mm to about 0.6 mm, or about 0.5 mm, about 0.6 mm, about 0.7 mm, about 0.8 mm, about 0.9 mm, about 1.0 mm, about 1.1 mm, about 1.2 mm, about 1.3 mm, about 1.4 mm, or any value or range within that range.
[0075] If the mass flow rate of the melt discharged onto the rotating wheel is 0.20 kg / min, the nozzle diameter can be 0.5 mm. If the mass flow rate of the melt discharged onto the rotating wheel is 0.50 kg / min, the nozzle diameter can be 0.7 mm. If the mass flow rate of the melt discharged onto the rotating wheel is 0.80 kg / min, the nozzle diameter can be 1.0 mm. If the mass flow rate of the melt discharged onto the rotating wheel is 1.30 kg / min, the nozzle diameter can be 1.2 mm. If the mass flow rate of the melt discharged onto the rotating wheel is 1.90 kg / min, the nozzle diameter can be 1.4 mm.
[0076] Step (ii) may comprise a melt spinning process.
[0077] The present disclosure also relates to magnetic materials comprising powders of alloys having the compositions disclosed herein or produced by the methods disclosed herein.
[0078] Additionally, the present disclosure relates to plastic bonded magnets comprising the magnetic materials disclosed herein. EXAMPLES
[0079] Non-limiting examples of the present invention will now be described in more detail with reference to specific examples, which should not be construed as limiting the scope of the invention in any way.
[0080] Example 1 - General alloy production method Weigh out the appropriate amount of raw materials (Nd, Fe, Co, Fe-B) according to the composition formula, with the total weight being 100 grams, and then charge all the raw materials into an arc melting furnace. Each raw material is melted under an argon atmosphere, and cooled to obtain an ingot, thereby producing Nd 11.6 Fe 80.3 Co 2.4 B 5.7 A rapidly solidified alloy with the composition was produced. An additional 1% Nd was added before melting to compensate for melting losses. The alloy ingot was turned over and remelted four times to ensure homogeneity.
[0081] The ingots were then crushed into pieces and placed in a crucible tube with a small nozzle at the bottom, which was then placed in a melt spinning apparatus. The alloy ingots were heated to remelt in an argon atmosphere and discharged onto a rotating metal wheel to form ribbons. The discharge temperature was about 1400°C to 1600°C, the discharge pressure was about 200 torr to 500 torr, the nozzle diameter was about 0.5 mm to 1.4 mm, and the wheel speed was about 20 m / s to 45 m / s. The ribbons were crushed into -40 mesh powder by a twin roller crusher.
[0082] In the same manner as above, Nd 11.9 Fe 81 Nb 1.2 B 5.9 A rapidly solidified alloy having the following composition was produced.
[0083] Then, the rapidly solidified Nd 11.6 Fe 80.3 Co 2.4B 5.7 Alloy powder and Nd 11.9 Fe 81 Nb 1.2 B 5.9 The magnetic properties of the alloy powders were measured by a Lakeshore vibrating sample magnetometer (VSM). A demagnetization factor of 0.21 was used to correct for the shape demagnetization effect in the powders. Figure 1a, Table 1 (Nd 11.6 Fe 80.3 Co 2.4 B 5.7 Alloy) and Figure 1b, Table 2 (Nd 11.9 Fe 81 Nb 1.2 B 5.9 The results are shown in Table 1.
[0084] [Table 1]
[0085] [Table 2]
[0086] As is clear from Tables 1 and 2, Nd 11.6 Fe 80.3 Co 2.4 B 5.7 Alloy and Nd 11.9 Fe 81 Nb 1.2 B 5.9 For both alloys, the lower the mass flow rate, the higher the magnetic properties (B r , H ci , and (BH) max ) was obtained. As can be seen from the demagnetization curve in Fig. 1, the squareness of the demagnetization curve (S q , (BH) max / B r 2 ), has been improved.
[0087] Referring to FIG. 2, as the mass flow rate decreases, (BH) max It was also found that the increase in the mass flow rate increased linearly by 7 kJ / m for every 1 kg / min decrease in the mass flow rate.3 ~9kJ / m 3 It was found that there was an increase in
[0088] Example 2 - Magnetic properties of various other alloys According to the method of Example 1, various rare earth metals (Nd, Pr, NdPr, La, Ce, etc.), various additives (Co, Nb, Zr, Al, etc.), and the structure REFe 14 Various other rapidly solidified alloys with various amounts of B phase were prepared. The (BH) of the rapidly solidified alloys was then subjected to various mass flow rates. max The results are shown in Table 3.
[0089] [Table 3]
[0090] As can be seen from Table 3, when melt-spun at low mass flow rates, the BH was significantly higher for all alloys. max By decreasing the mass flow rate from 1.9 kg / min to 0.2 kg / min, (BH) max at 6 kJ / m 3 ~14kJ / m 3 It was found that an increase in
[0091] Example 3 - Wheel Speed vs. Mass Flow Rate It has been found that the wheel speed can be adjusted to achieve optimal cooling of the alloy ribbon. By "optimal quenching" it is meant that by adjusting the wheel speed, the ribbon is quenched at an optimal cooling rate such that the resulting alloy ribbon has the finest, most uniform nanoscale grains and therefore the highest magnetic properties. On the other hand, "under quenching" refers to a cooling rate that is too slow, resulting in grain sizes that are too large, and "over quenching" refers to a cooling rate that is too fast, resulting in the formation of amorphous phases. Both under quenching and over quenching result in degraded magnetic properties.
[0092] From Figure 3 and Table 4, the wheel speed for optimal quenching is Nd11.6 Fe 80.3 Co 2.4 B 5.7 For alloys, the range is 20m / sec to 45m / sec, and for Nd 11.9 Fe 81 Nb 1.2 B 5.9 For alloys, it can be seen to be in the range of 15 m / s to 30 m / s. As the mass flow rate increased, the wheel speed increased.
[0093] [Table 4]
[0094] Example 4 - Ribbon Size vs Mass Flow Rate The dimensions of the alloy ribbons were measured for all alloy ribbons at various mass flow rates. As can be seen from Figure 4a and Table 5, the Nd 11.6 Fe 80.3 Co 2.4 B 5.7 In the case of the alloys, the ribbon thickness measured from the ribbon surface in contact with the rotating wheel surface (wheel side) to the ribbon free surface not in contact with the rotating wheel surface (free side) ranged from 28 μm to 32 μm, and the ribbon width measured from the left end of the ribbon to the right end of the ribbon ranged from 1 mm to 4 mm.
[0095] [Table 5]
[0096] As can be seen from Figure 4b and Table 6, Nd 11.9 Fe 81 Nb 1.2 B 5.9 For the alloys, the ribbon thickness ranged from 35 μm to 47 μm, and the ribbon width ranged from 1 mm to 4 mm.
[0097] [Table 6]
[0098] The dimensions of the various alloy ribbons at various mass flow rates are further summarized in Table 7. It was found that higher mass flow rates resulted in larger ribbon widths, but no significant change in ribbon thickness.
[0099] [Table 7]
[0100] The most important observation from Tables 5-7 is that the higher the mass flow rate, the larger the ribbon width (about 260% increase) when the mass flow rate is increased from 0.2 kg / min to 1.9 kg / min, but there is no significant change in ribbon thickness (only 10%-35% increase) when the mass flow rate is increased from 0.2 kg / min to 1.9 kg / min. This behavior has an important impact on the microstructural homogeneity of the quenched ribbons, which is discussed further in Example 7.
[0101] Example 5 - RE2Fe vs. Mass Flow Rate 14 B Crystalline phase ratio As mentioned above, the alloys disclosed herein contain, as their main constituent phase, RE2Fe 14 B phase. In the melt spinning process, RE2Fe 14 The entire B phase is made up of very fine and uniform RE2Fe 14 It is desirable to uniformly quench the alloy so that it solidifies into B particles. Under these conditions, RE2Fe 14 The volume fraction of the B crystalline phase is also maximized. In other words, RE2Fe 14 The higher proportion of B crystalline phase indicates that the alloy ribbon is quenched more uniformly.
[0102] At various mass flow rates, RE2Fe 14 The volume fraction of the RE2Fe B crystalline phase was measured. 14 A higher volume fraction of the B crystalline phase was found, indicating that the lower mass flow rate resulted in more uniform quenching.
[0103] As can be seen from Fig. 5 and Table 8, the as-quenched Nd 11.6 Fe 80.3 Co 2.4 B 5.7 More than 98% by volume of the alloy powder is crystalline RE2Fe 14 It was phase B, with the remaining volume percent being amorphous.
[0104] [Table 8]
[0105] Example 6 - Average particle size of ribbons and average particle size of crushed powder versus mass flow rate X-ray diffraction (XRD) tests were performed on the alloy ribbons and crushed powders produced with various mass flow rates. For example, Nd 11.6 Fe 80.3 Co 2.4 B 5.7 A typical XRD pattern of the alloy powder is shown in Figure 6. All peaks are from NdFe 14 It was found that the crystalline phase may represent the NdFe 14 This means that the phase is B-type. Significant peak broadening was also observed. This is due to the fact that Nd2Fe 14 This indicates that the grain size of phase B is very small.
[0106] Scherrer's formula: Average particle size=Kλ / βcosθ where K is a dimensionless form factor and has a typical value of about 0.9, λ is the X-ray wavelength and has a value of 1.5405 Å when the X-ray source is CuKα, β is the full width at half maximum (FWHM) in radians, and θ is the Bragg angle. 14 The grain size of the B phase can be calculated.
[0107] As mentioned above, the Scherrer equation was used to calculate the RE2Fe 14 The grain size of the B phase was calculated. As can be seen from Fig. 7 and Table 9, the grain size of Nd 11.6 Fe 80.3 Co2.4 B 5.7 The average particle size of the alloy crushed powder was about 20 nm to 30 nm. It was further found that a lower mass flow rate resulted in a smaller particle size, which in turn resulted in higher magnetic properties, as seen in Examples 1 and 2. However, the particle size difference between the wheel side of the alloy ribbon and the free side of the alloy ribbon was almost the same at different mass flow rates. This can be seen from the ribbon thickness data shown in Example 4, where it was found that the ribbon thickness remained essentially unchanged as the mass flow rate was changed. Since the particle size difference between the wheel side and the free side of the ribbon is mainly caused by the difference in cooling rate between the wheel side and the free side, which is proportional to the ribbon thickness, the almost unchanged ribbon thickness at various mass flow rates indicates that the particle size difference between the wheel side and the free side of the ribbon is similar.
[0108] [Table 9]
[0109] Example 7 - Particle size uniformity across the ribbon As mentioned above, uniform grain size along the ribbon width direction (from the left edge of the ribbon to the center and then to the right edge) is important to achieve high performance alloy ribbons. In this example, a field emission scanning electron microscope (SEM) was used to observe ribbon cross-sectional regions from the left edge of the ribbon to the center and then to the right edge. The RE2Fe 14 The average grain size of B phase was calculated using ImageJ software (Image Processing and Analysis in Java, http: / / rsb.info.nih.gov.ij, version 1.51j8), and the results are summarized in Figure 8, Figure 9, and Table 10. It was found that a lower mass flow rate produced a more uniform grain size when measured along the width of the alloy ribbon.
[0110] Fig. 10 is an exemplary diagram showing the regions that make up the width of the alloy ribbon of the present invention. As can be seen from Fig. 10, the left end of the alloy ribbon is made up of the first 5% of the width (i.e., 0% to 5%), the center left portion is made up of the next 30% of the width (i.e., 5% to 35%), the center portion is made up of the next 30% of the width (i.e., 35% to 65%), the center right portion is made up of the next 30% of the width (i.e., 65% to 95%), and the right end portion of the alloy ribbon is made up of the last 5% of the width (i.e., 95% to 100%).
[0111] As can be seen from Figs. 8, 9 and Table 10, Nd 11.6 Fe 80.3 Co 2.4 B 5.7 For the alloy ribbons, the grain size ranged from 21 nm to 27 nm, and the grain size difference between the center and the left and right ends was only 2% to 4% at a mass flow rate of 0.2 kg / min, 8% to 12% at a mass flow rate of 0.5 kg / min, and 17% to 19% at a mass flow rate of 0.8 kg / min, respectively, and the grain size from the left end to the right end became more uniform with lower mass flow rates from 0.2 kg / min to 0.8 kg / min.
[0112] However, at the higher mass flow rates of 1.3 kg / min and 1.9 kg / min, the particle size was in the range of 15 nm–29 nm, and the difference in particle size between the center and the left and right ends was 27%–31% at a mass flow rate of 1.3 kg / min and 36%–48% at a mass flow rate of 1.9 kg / min, indicating that the particles at both ends were significantly smaller than those at the center.
[0113] Thus, it is clear that the lower mass flow rate results in a much more uniform grain size when measured along the width of the alloy ribbon. This indicates that the lower mass flow rate results in a more uniform cooling rate along the ribbon width, while the higher mass flow rates result in less uniformity. Specifically, at higher mass flow rates, the edge regions cool faster than quenching (i.e., too fast) resulting in grains that are too small or partially amorphous (meaning no grains at all). The center cools less than quenching (i.e., too slow) resulting in very large grains. This is in good agreement with the significant increase in ribbon width with mass flow rate as shown in Example 4. From the perspective of heat transfer between the alloy ribbon and the quench wheel, it is believed that the narrow ribbons produced at lower mass flow rates have a more uniform temperature along the ribbon width and therefore a uniform cooling rate. However, it is believed that the edge regions of the wider ribbons have a lower temperature than the center because they are farther from the heat source (i.e., alloy flow). It is believed that this results in a non-uniform cooling rate, with the edges cooling much faster than the center.
[0114] [Table 10] [Industrial Applicability]
[0115] Advantageously, the alloy compositions, magnetic materials, and bonded magnets of the present disclosure have improved magnetic properties, e.g., high B r Value, high (BH) max value, and high H ci The value may be indicated.
[0116] Advantageously, the disclosed methods of making the disclosed alloys may produce alloys having a substantially uniform ribbon microstructure.
[0117] More advantageously, according to the method of the present disclosure, RE2Fe 14 It is possible to produce alloys having a predominantly B phase.
[0118] Even more advantageously, the methods of the present disclosure provide for substantially uniform quenching.
[0119] Various other modifications and adaptations of the present invention will become apparent to those skilled in the art upon reading the foregoing disclosure without departing from the spirit and scope of the present invention, and all such modifications and adaptations are intended to be within the scope of the appended claims.
Claims
1. Formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and and B is boron. The alloy contains at least 80% by volume of RE. 2 Fe 14 Including phase B, The RE 2 Fe 14 The average grain size of the B phase is in the range of about 20 nm to about 40 nm, and The alloy is an alloy ribbon having a width measured from the left end to the center to the right end, and the RE between the center of the alloy ribbon and the left and right ends. 2 Fe 14 An alloy, wherein the difference in average grain size of the B phase is less than 20%.
2. At least 98% by volume of RE 2 Fe 14 10. The alloy of claim 1 comprising a B phase.
3. 3. The alloy of claim 1 or 2, wherein a left end of the alloy ribbon comprises greater than 0% to 10% of the width, a right end of the alloy ribbon comprises greater than 0% to 10% of the width, and a central portion of the alloy ribbon comprises about 1% to 40% of the width.
4. RE in the center of the alloy ribbon 2 Fe 14 The average grain size of the B phase is in the range of about 25 nm to about 40 nm, and the RE at the left and right ends of the alloy ribbon 2 Fe 14 The alloy of any one of claims 1 to 3, wherein the average grain size of the B phase is from about 20 nm to about 30 nm.
5. 5. The alloy of any one of claims 1 to 4, wherein RE is one or more rare earth metals selected from the group consisting of lanthanum (La), cerium (Ce), neodymium (Nd), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), and ytterbium (Yb).
6. RE is the following: (i) Nd, (ii) Nd, Pr, (iii) Nd, Pr, La, (iv) Nd, Pr, Ce, (v) Nd, Pr, La, Ce, (vi) Nd, La, (vii) Nd, Ce, (viii) Nd, Ce, La, (ix) Pr, (x) Pr, La, (xi) Pr, Ce, and (xii) Pr, La, Ce The alloy of any one of claims 1 to 5, selected from the group consisting of:
7. 7. The alloy of any one of claims 1 to 6, wherein M is absent or is one or more metals selected from the group consisting of zirconium (Zr), niobium (Nb), molybdenum (Mo), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), hafnium (Hf), tantalum (Ta), tungsten (W), cobalt (Co), copper (Cu), gallium (Ga), and aluminum (Al).
8. The compound of formula (I) is as follows: (i) Nd-Fe-Nb-B, (ii) Nd-Fe-Co-B, (iii) (NdPrLa)-Fe-Al-B, (iv) (NdPr)-Fe-Zr-B, (v) (NdPrCe)-Fe-Zr-B, (vi) Nd-Fe-Co-B, (vii) Nd-Fe-B, (viii) (NdPr)-Fe-B, (ix) (NdPrLaCe)-Fe-B, (x) (NdPr)-Fe-Co-B, and (xi) (NdPr)-Fe-Nb-B The alloy of any one of claims 1 to 7, selected from the group consisting of:
9. An alloy according to any one of claims 1 to 8, containing less than 10 atomic % boron.
10. The compound of formula (I) has the formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and 10. The alloy of any one of claims 1 to 9, wherein x, y, and z are in atomic percent and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.
0.
11. Formula (I): RE-Fe-MB Formula (I) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; and and B is boron, comprising the steps of: (i) discharging a melt of an alloy having a composition of formula (I) onto a rotating wheel at a mass flow rate ranging from about 0.2 kg / min to about 1.0 kg / min; (ii) quenching the melt using the rotating wheel to obtain an alloy ribbon; A method comprising:
12. The method of claim 11, wherein the wheel is rotated at a speed in the range of about 20 m / sec to about 45 m / sec.
13. 13. The method of claim 11 or 12, wherein the melt is discharged onto the rotating wheel through one or more nozzles, and the mass flow rate is controlled by controlling the diameter of the nozzles.
14. The method of claim 13, wherein the nozzle has a diameter in the range of about 0.5 mm to about 1.4 mm.
15. The method of any one of claims 11 to 14, wherein step (ii) comprises a melt spinning process.
16. The alloy is at least 80% by volume of RE 2 Fe 14 The method of any one of claims 11 to 15, comprising a phase B.
17. The alloy is at least 98% by volume RE 2 Fe 14 The method of any one of claims 11 to 16, comprising a phase B.
18. The RE 2 Fe 14 18. The method according to claim 16 or 17, wherein the average grain size of the B phase is in the range of about 20 nm to about 40 nm.
19. The alloy ribbon has a width measured from the left end to the center to the right end, and the RE between the center of the alloy ribbon and the left and right ends. 2 Fe 14 The method according to any one of claims 16 to 18, wherein the difference in average grain size of phase B is less than 20%.
20. RE in the center of the alloy ribbon 2 Fe 14 The average grain size of the B phase is in the range of about 25 nm to about 40 nm, and the RE at the left and right ends of the alloy ribbon 2 Fe 14 20. The method of claim 19, wherein the average grain size of the B phase is from about 20 nm to about 30 nm.
21. The method of any one of claims 11 to 20, wherein the alloy ribbon has a thickness in the range of about 20 μm to about 50 μm.
22. The method of any one of claims 11 to 21, wherein the alloy ribbon has a width in the range of about 1 mm to about 5 mm.
23. 23. The method of any one of claims 11 to 22, wherein RE is one or more rare earth metals selected from the group consisting of lanthanum (La), cerium (Ce), neodymium (Nd), praseodymium (Pr), yttrium (Y), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), and ytterbium (Yb).
24. RE is the following: (i) Nd, (ii) Nd, Pr, (iii) Nd, Pr, La, (iv) Nd, Pr, Ce, (v) Nd, Pr, La, Ce, (vi) Nd, La, (vii) Nd, Ce, (viii) Nd, Ce, La, (ix) Pr, (x) Pr, La, (xi) Pr, Ce, and (xii) Pr, La, Ce The method according to any one of claims 11 to 23, wherein the compound is selected from the group consisting of:
25. 25. The method of any one of claims 11 to 24, wherein M is absent or is one or more metals selected from the group consisting of zirconium (Zr), niobium (Nb), molybdenum (Mo), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), hafnium (Hf), tantalum (Ta), tungsten (W), cobalt (Co), copper (Cu), gallium (Ga), and aluminum (Al).
26. The compound of formula (I) is as follows: (i) Nd-Fe-Nb-B, (ii) Nd-Fe-Co-B, (iii) (NdPrLa)-Fe-Al-B, (iv) (NdPr)-Fe-Zr-B, (v) (NdPrCe)-Fe-Zr-B, (vi) Nd-Fe-Co-B, (vii) Nd-Fe-B, (viii) (NdPr)-Fe-B, (ix) (NdPrLaCe)-Fe-B, (x) (NdPr)-Fe-Co-B, and (xi) (NdPr)-Fe-Nb-B The method according to any one of claims 11 to 25, selected from the group consisting of:
27. A method according to any one of claims 11 to 26, wherein the alloy after rapid solidification comprises less than 10 atomic % boron.
28. The compound of formula (I) has the formula (Ia): RE x -Fe (100-x-y-z) -M y -B z Formula (Ia) (In the formula, RE is one or more rare earth metals; Fe is iron, M is absent or is one or more metals; B is boron, and 28. The alloy of any one of claims 11 to 27, wherein x, y, and z are in atomic percent and 8.0≦x≦14.0, 0≦y≦2.0, and 5.0≦z≦7.
0.
29. A magnetic material comprising a powder of the alloy according to any one of claims 1 to 10, or a powder of an alloy ribbon produced by the method according to any one of claims 11 to 28.
30. 30. A plastic bonded magnet comprising the magnetic material of claim 29.